Instructional coaches and the instructional leadership team a guide for school-building improvement - Spaulding, Dean T.; Smith, Gail (Gail M.) (Thousand Oaks, Calif. : Corwin, 2012)
For instructional coaches, no two days are ever the same. This unique companion melds theory and practice to show how coaches can seamlessly integrate themselves into the fabric of the school and help teachers improve their practice from day one. Dean Spaulding and Gail Smith address common challenges of coaches and instructional leadership teams. Journal entries based on the real-life experiences give an inside look at the day-to-day work of an instructional coach and the power of coaching to improve teacher effectiveness.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: School supervision -- United States -- Handbooks, manuals, etc; Educational leadership -- United States -- Handbooks, manuals, etc; School management and organization -- United States; School improvement programs -- United States